Role Grónska a Nunavutu v mezinárodních vztazích v letech 1979-2009 - Zettlitzerová, Radka (Univerzita Karlova, Fakulta sociálních věd, 2013)
Greenland and Nunavut are territories with a limited measure of autonomy. Greenland obtained it's autonomy when the Greenland Home Rule Act came into effect. Nunavut instead, obtained it's autonomy from the moment it was created in 1999, via the Nunavut Land Claims Agreement and the Nunavut Act. Both Greenland and Nunavut have no authority to interfere with international affairs, but they do have options to get involved via different Inuit organizations (the majority of the population both Greenland and Nunavut are Inuits). This bachelor thesis, Role of Greenland and Nunavut in international relations in 1979 - 2009, aims to find an answer to the possibility of Greenland and Nunavut having an active part in international affairs (based on the documents mentioned above), if they can be considered of subjects of the international law and if some examples of their international involvement even can be mentioned. Even though according to their constitutional acts, niether Greenland nor Nunavut are allowed to act independently in matters of international affairs, the author of this thesis defends the hypothesis that in fact they can, participate in international discussions and even, on a limited scale, decide their own foreign policy. The first part of this thesis introduces a basic geographical,. Grónsko a Nunavut jsou území s určitou mírou samosprávy. Grónsko získalo svůj autonomní statut v roce 1979, když vstoupil v platnost Zákon o grónské samosprávě, a v případě Nunavutu se tak stalo s jeho vznikem v roce 1999 na základě dokumentů Dohody o územních požadavcích Nunavutu a Zákonu o Nunavutu. V pravomocích obou autonomií sice nejsou záležitosti spojené se zahraniční politikou, ale existují možnosti, jak se Grónsko a Nunavut mohou v mezinárodních vztazích angažovat - například prostřednictvím iniciativ Inuitů, většinových obyvatel Grónska i Nunavutu. Bakalářská práce Role Grónska a Nunavutu v mezinárodních vztazích v letech 1979 - 2009 se snaží odpovědět na otázku, zda výše zmíněné dokumenty umožňují Grónsku a ...